Why do people dislike low-wage trade competition with posted workers in the service sector? - Lars Calmfors; Girts Dimdins; Marie Gustafsson Sendén; Henry Montgomery; Ulrika Stavlöt (Center for Economic Studies and ifo Institute (CESifo), 2012)
The issue of low-wage competition in services trade involving posted workers is controversial in the EU. Using Swedish survey data, people's attitudes are found to be more negative to such trade than to goods trade. The differences depend on both a preference for favouring social groups to which individuals belong (here the domestic population) and altruistic justice concerns for foreign workers. In small-group experiments we find a tendency for people to adjust their evaluations of various aspects of trade to their general attitude. This tendency is stronger for those opposed to than those in favour of low-wage trade competition. This may indicate that the former group forms its attitudes in a less rational way than the latter group.
Keywords: F16; D01; 330; services trade; posted workers; wage regulations; attitude formation; Niedriglohn; Meinung; Internationaler Dienstleistungsverkehr; Internationale Arbeitsmobilität; Internationaler Wettbewerb; Schweden